2018
DOI: 10.5194/acp-18-9803-2018
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of contrail to cirrus evolution during the Contrail and Cirrus Experiment (CONCERT)

Abstract: Abstract. Air traffic affects cloudiness, and thus climate, by emitting exhaust gases and particles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 89 publications
3
26
0
Order By: Relevance
“…The measured angular scattering functions are flat and featureless. Studies with optical particle models (Doutriaux-Boucher et al, 2000;C-Labonnote et al, 2001;Baum et al, 2010;Jourdan et al, 2010;Yang et al, 2013;Liu et al, 2014a, b;Letu et al, 2016;Tang et al, 2017) show that the flattening of the angular scattering function at the sideward angles can be reproduced by ice particles with a high degree of crystal complexity, which is in accordance with our observations. More importantly, the ensemble angular scattering functions at both solar wavelengths are almost identical irrespective of the geographical location.…”
Section: Measurements Of the Angular Scattering Functionsupporting
confidence: 91%
See 1 more Smart Citation
“…The measured angular scattering functions are flat and featureless. Studies with optical particle models (Doutriaux-Boucher et al, 2000;C-Labonnote et al, 2001;Baum et al, 2010;Jourdan et al, 2010;Yang et al, 2013;Liu et al, 2014a, b;Letu et al, 2016;Tang et al, 2017) show that the flattening of the angular scattering function at the sideward angles can be reproduced by ice particles with a high degree of crystal complexity, which is in accordance with our observations. More importantly, the ensemble angular scattering functions at both solar wavelengths are almost identical irrespective of the geographical location.…”
Section: Measurements Of the Angular Scattering Functionsupporting
confidence: 91%
“…Field measurements of ice crystal mesoscopic complexity were taken between 2011 and 2017 in the Mid-latitude Airborne Cirrus Properties Experiment (MACPEX) (Jensen et al, 2013), the Mid Latitude Cirrus (ML-CIRRUS) campaign (Voigt et al, 2017), the Aerosol, Cloud, Precipitation, and Radiation Interactions and Dynamics of Convective Cloud Systems Cloud processes of the main precipitation systems in Brazil: A contribution to cloud resolving modeling and to the GPM (GlobAl Precipitation Measurement) (ACRIDICON-CHUVA) campaign (Wendisch et al, 2016), the Radiation-Aerosol-Cloud Experiment in the Arctic Circle (RACEPAC) campaign (Costa et al, 2017) and the Arctic CLoud Observations Using airborne measurements during polar Day (ACLOUD) campaign (Wendisch et al, 2018). The field measurements of angular scattering functions were taken between 1998 and 2017 in the Interhemispheric Dif-ferences in Cirrus Properties from Anthropogenic Emissions (INCA) project (Shcherbakov et al, 2005), the midlatitude campaign CIRRUS'98 (Jourdan et al, 2003), the Arctic Study on Tropospheric Aerosol and Radiation (ASTAR) campaign (Jourdan et al, 2010), the Contrail and Cirrus Experiments (CONCERT) 1 and 2 (Chauvigné et al, 2018), the tropical campaign ACRIDICON-CHUVA, the Airborne Research Instrumentation Testing Opportunity (ARISTO2017), the Arctic campaign ACLOUD and, the Southern Ocean Clouds, Radiation, Aerosol Transport Experimental Study (SOCRATES).…”
Section: Sampled Clouds and Definitionsmentioning
confidence: 99%
“…The instrument was mounted next to the CO 2 inlet on the upper side of the DC-8 fuselage. The probe has been previously used for contrail measurements (Voigt et al, 2010(Voigt et al, , 2011Gayet et al, 2012;Chauvigné et al, 2018), and its electronics received an update in 2017, such that the recording of single-particle data is possible. The sampling area of 0.19 mm 2 was determined by laboratory calibrations, and the instrument was size-calibrated on the basis of a Tmatrix calculation for an ice particle aspect ratio of 0.5 (Borrmann et al, 2000;Luo et al, 2003;Rosenberg et al, 2012).…”
Section: Particle and Trace Gas Measurementsmentioning
confidence: 99%
“…Kleine et al (2018) assessed the sublimation effects with data of the ECLIF I experiment and showed that both soot and ice particle number concentrations are a function of the position behind and below the contrailing aircraft. An overview of contrail observations has been compiled by , and microphysical data on aged contrail cirrus have been analysed by Voigt et al (2017) and Chauvigné et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The instrument was mounted next to the CO 2 inlet on the upper side of the DC-8 fuselage. The probe has been previously used for contrail measurements during multiple recent studies (Chauvigné et al, 2018;Gayet et al, 2012;Voigt et al, 2010Voigt et al, , 2011, and its electronics received an update in 2017, such that the recording of single particle data is possible. The sampling area of 0.19 mm 2 was determined by laboratory calibrations and the instrument was size-calibrated on the basis of a T-Matrix calculation for an ice particle aspect ratio of 0.5 (Borrmann et al, 2000;Luo et al, 2003;Rosenberg et al, 2012).…”
Section: Particle and Trace Gas Measurementsmentioning
confidence: 99%